HOSPITAL-ACQUIRED CATHETER-ASSOCIATED URINARY TRACT INFECTIONS AT THE INTENSIVE CARE CENTER, BACH MAI HOSPITAL, DURING 2024–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the incidence and microbial etiology of catheter-associated urinary tract infections (CAUTI) at the Intensive Care Center, Bach Mai Hospital, during the period 2024–2025. Methods: A prospective observational descriptive study was conducted using convenient sampling. All patients who had a urinary catheter placed between July 2024 and August 2025 were included, excluding those with urinary tract infection before admission or within the first 48 hours of hospitalization. CAUTI was diagnosed according to the CDC 2024 criteria. Clinical data were obtained from medical records, and statistical analyses were performed using SPSS software. Results: Among 575 catheterized patients, 34 cases (5.9%) developed catheter-associated urinary tract infection, including 31 symptomatic cases (5.0%) and 3 asymptomatic cases (0.9%). The incidence rate of CAUTI was 6.3 cases per 1,000 catheter-days. Most CAUTI patients were female (67.6%) and aged >65 years (50.0%), with a mean age of 59.8 ± 17.6 years.Regarding microbial etiology, Candida spp. predominated (67.6%), with Candida albicans (35.3%) and Candida tropicalis (26.5%) being the most common species. Enterococcus faecium accounted for 23.5%, while Gram-negative bacteria were less frequently isolated.Conclusion: The CAUTI prevalence was 5.9%, with an incidence rate of 6.3 per 1,000 catheter-days. The predominant causative pathogens were Candida species and Enterococcus faecium.
Keywords: Catheter-associated urinary tract infection, urinary catheter, CAUTI, Candida tropicalis, Enterococcus faecium, intensive care.